Pelatihan Kewirausahaan bagi Wirausaha Baru Berbasis Potensi Lokal di Kecamatan Sempor Kabupaten Kebumen - Firmansyah, Irman; Kemala Octisari, Sully; Arif Sapta, Yuniarto; Roni, Budianto; Wahyudin, Wahyudin; Lestari, Puji (LP3M Universitas Putra Bangsa, 2023)
This program is intended to give birth and grow new entrepreneurs in Sempor District, Kebumen Regency. This is because the portrait of the potential of agricultural products which can be a source of MSME entrepreneurial products has not been properly utilized. New entrepreneurs can be a solution to exploit this potential. But until now, the understanding of entrepreneurship for the community is still minimal. Therefore, this activity is intended to provide new entrepreneurs with an understanding of the important aspects of entrepreneurship. The method used is training with a two-way form. The material discussed in this activity consisted of: general understanding of entrepreneurship and motivation, exploiting local potential for superior products, and strategies so that MSME businesses can run sustainably.